1994
DOI: 10.1038/icb.1994.69
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A incompatibility associated with enhanced long‐term renal graft survival in HLA‐B, DR mismatched transplants

Abstract: SummaryThe effect of HLA-A matching on long-term cadaver kidney graft survival was analysed, on average, 6 years after transplantation in a total of 1085 cyclosporine (CyA)-treated patients.A beneficial effect of HLA-A mismatching on graft survival was found by univariate and multivariate analyses (?< 0.05).Enhanced graft survival was associated with HLA-A mismatching in transplants mismatched for HLA-B,DR (/*= 0.03), but not in HLA-B,DR compatible transplants.High 6 year graft survival rates, 78% and 66%. wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Bucin et al 14 previously showed a favorable effect of HLA-A–incompatible grafts on long-term renal graft survival in cyclosporine (CYA)-treated recipients of HLA-B,DR–incompatible transplants. It was hypothesized that incompatibility between donor and recipient for HLA-A–related antigens induces a downregulatory reaction on the immune response to incompatible HLA-B and HLA-DR antigens.…”
mentioning
confidence: 99%
“…Bucin et al 14 previously showed a favorable effect of HLA-A–incompatible grafts on long-term renal graft survival in cyclosporine (CYA)-treated recipients of HLA-B,DR–incompatible transplants. It was hypothesized that incompatibility between donor and recipient for HLA-A–related antigens induces a downregulatory reaction on the immune response to incompatible HLA-B and HLA-DR antigens.…”
mentioning
confidence: 99%